The influences of group dialog on individual student understanding of science concepts - Abdi-Rizak M. Warfa; James Nyachwaya; Gillian Roehrig (SpringerOpen, 2018)
Abstract Background Cooperative and inquiry-based pedagogies provide a context for classroom discourse in which students develop joint understanding of subject matter knowledge. Using the symbolic interactionist perspective that meaning is constructed as individuals interact with one another, we examined how student groups enrolled in an undergraduate general chemistry course developed sociochemical norms that influenced individual student understanding of chemical concepts. Sociochemical norms refer to the normative aspects of classroom microculture that regulate discourse on what counts as a table chemical justification and explanation. We describe how these sociochemical normative ideas were developed based on observational research and recordings of the student groups as they engaged in classroom discourse. Results Our analysis showed that students routinely developed chemistry-driven criteria within and across groups to explain the nature of dissolving ionic solids in water. Moreover, resultant sociochemical norms led to shifts in student understanding and the ways in which students reasoned about the causes of chemical phenomena under study. Conclusions Our results indicate that group dialog influenced individual student conceptions of ionic compounds in solution and highlight the need to engage students in instructional activities that not only engage them in the multiple ways of representing chemical knowledge but also making public their views and participating in classroom discourse.